Trajectories of Cardiac Allograft Vasculopathy After Heart Transplantation and association with mortality: a population-based study. (25th November 2020) - Bonnet, G; Coutance, G; Van Keer, J; Raynaud, M; Aubert, O; Bories, M.C; Bruneval, P; Varnous, S; Leprince, P; Empana, J.P; Naesens, M; Patel, J.K; et al.
Abstract: Background: Cardiac allograft vasculopathy (CAV) is a major contributor of heart transplant recipient's mortality. However, the associations between CAV trajectories and mortality remains poorly described. Purpose: We aimed to identify the different evolutive profiles of CAV and to determine the respective association with all-cause mortality. Methods: Heart transplant recipients receiving care at 4 academic centers were included. Patients underwent prospective, protocol-based monitoring consisting of repeated coronary angiographies together with systematic assessment of clinical, functional, histological and immunological parameters. The mainoutcome was a prediction for CAV trajectories using unsupervised latent class mixed models. We then identified their association with all-cause mortality (NCT04117152). Results: Overall, 1, 301 patients were included (815 and 486 in the development and validation cohorts, respectively). The median follow-up post-transplant was 6.6 years (IQR=4.7) with 4, 710 coronary angiographies analyzed (3.6±1.6 CAV assessments per patient). We identified 4 distinct profiles of CAV trajectories over 10 years that were characterized by i)Patients without CAV at baseline and non-progression (n=823, 63.3%), ii) patients without CAV at baseline and late onset CAV progression (n=79, 6.1%), iii) patients with mild baseline CAV and mild progression (n=261, 20.1), iv) patients with mild baseline CAV and accelerated CAV progression (n=138, 10.6%, discrimination 0.95). The 4 CAV trajectories showed gradient for all-cause mortality (p<0.001). Trajectories #3 and #4 were associated with higher mortality rates (10-year patient survival of 73.43% [95% CI 65.18–80.02] and 51.89% [95% CI 38.76–63.51], respectively) as compared with trajectories #1, and #2 that were characterized by 10-year patient survival of 80.01 [95% CI 76.38–84.82] and 83.49% [95% CI 71.34–90.80], respectively (p<0.001). Conclusion: In a large multicentric and highly phenotyped prospective cohort of heart transplant recipients, we identified 4 robust CAV trajectories. These different profiles were associated with distinct prognosis. Our results provide the basis for a trajectory-based assessment of heart transplant patients for early patient risk stratification and patient monitoring. Funding Acknowledgement: Type of funding source: None